Implementation of Counseling Guidance and Discipline on the Sports Motivation of Generation Z Students (Literature Review Sport Education) - Silviah, Reni (Journal of Law, Politic and Humanities, 2021)
Literature review The implementation of guidance and counseling and discipline on the sport motivation of Generation Z students is a scientific article aimed at analyzing whether sports motivation plays a role in discipline and counseling guidance. A qualitative approach using descriptive study (literature review) was employed to explore and analyze the relationship between counseling guidance, discipline, and exercise motivation. The results of this article are: 1) Discipline plays a role in sports motivation, 2) Counseling guidance plays a role in sports motivation. Besides these 2 exogenous variables that influence the endogenous variable of character formation, there are still many other factors including the quality of education, physical activity, and leadership.